Effect of Personal Branding on Perceived Employability: The Mediating Role of Self-Efficacy and the Moderating Role of Career Adaptability among Final-Year Students - Aura Ashelia; Syahrizal (Jurnal Informatika Ekonomi Bisnis, 2026)
In an era of intensifying labor market competition and widespread degree inflation, understanding the psychological and strategic factors that shape graduates' perceived employability has become a critical scholarly concern. This study investigates the role of personal branding in predicting perceived employability among final-year undergraduate students, with self-efficacy as a mediating mechanism and career adaptability as a moderating boundary condition. A quantitative, cross-sectional design was employed, with data collected from 400 final-year students at a Universitas Negeri Padang in West Sumatra, Indonesia, using a structured Likert-scale questionnaire. Hypotheses were tested using Structural Equation Modeling–Partial Least Squares. The results demonstrate that personal branding exerts a significant positive influence on both perceived employability and self-efficacy. Self-efficacy, in turn, significantly predicts perceived employability and fully mediates the personal branding–employability relationship. Furthermore, career adaptability positively moderates this pathway, amplifying the effect of personal branding on perceived employability among students with higher adaptive capacity. These findings extend Social Cognitive Career Theory by elucidating the sequential and conditional mechanisms linking self-presentation strategies to employability perceptions. Practically, the results highlight the importance of integrating personal branding development and self-efficacy enhancement into university career preparation programs.